Critical Success Factors for the Success of Strategic Projects in the Finnish Public Sector - SAHA, NILADRI (My University, 2026)
This thesis has examined the critical success factors that best contribute to success in Finnish public-sector strategic projects. The basis for the study is that success in public projects cannot be solely evaluated through time, cost and scope. In addition to producing short- term results (time, cost, and scope), public projects are expected to create long-term value, support organizational strategic objectives, utilize public resources effectively and provide added-value for society as a whole. As such, the study will apply a six-criterion model for evaluating project success including: efficiency, effectiveness, relevance, sustainability, value-for-money and broader societal impacts. In terms of methodology, the research has been completed in two phases. The first phase involved conducting a systematic literature review in order to identify the most commonly cited critical success factors from previous studies on public projects; governance; procurement; risks; sustainability etc. A preliminary framework consisting of five major do-mains was then constructed: Governance & Leadership; Procurement; Risk & Front-End Planning; Digital & Data Governance; Sustainability & Life cycle Value. In the second phase, a qualitative web-based survey was used to gather information from professionals who have worked in the Finnish public sector. The survey resulted in the completion of four web-form surveys, which were analysed using thematic content analysis. Findings indicate that success in Finnish public-sector strategic projects is dependent upon having a combination of several interrelated elements rather than relying on a singular element. Most importantly, they included: effective governance/governance and clear active governance; effective front-end definition/preparation; procurement capabilities that go beyond low-cost/lowest price criteria; capable personnel/people and communications; consideration of life cycle value/sustainability during project development. Findings also indicated that these factors are influenced by the specific nature of the Finnish public sector's regulatory environment. Specifically, legislative requirements/procedural rules/transparency requirements and limited flexibility once key decisions have been made all impact how project development occurs in the public sector. In conclusion, multi-criteria success in Finnish public-sector strategic projects appears to occur when projects are well-defined at their outset, actively managed throughout the project life cycle, supported by skilled individuals and teams, and ac-quired through procurement processes that consider both long-term value creation and compliance with relevant regulations. Overall, the primary contribution of this the-sis is to present a revised Finland-specific framework of critical success factors for stra-tegic public-sector projects that incorporates practitioner experience/evidence from academic literature. Practical recommendations for enhancing the planning/delivery of strategic public-sector projects within Finland are presented.
Keywords: public sector; projects; public administration; project management; project leadership; leadership (activity); evaluation; public procurement; success factors; success; Strategic Project Management; Master’s Programme in Industrial Engineering and Management